2019
DOI: 10.1038/s41598-019-51562-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of drug resistant Mycobacterium tuberculosis isolates from a high burden tuberculosis region of North West Pakistan

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis bacteria, is a leading infectious cause of mortality worldwide, including in Pakistan. Drug resistant M. tuberculosis is an emerging threat for TB control, making it important to detect the underlying genetic mutations, and thereby inform treatment decision making and prevent transmission. Whole genome sequencing has emerged as the new diagnostic to reliably predict drug resistance within a clinically relevant time frame, and its deployment will have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…In the present study, among 27 SLID resistant isolates, the most frequent mutation detected was rrs A1401G (40.7%), which was consistent with the reports from China, 4,6,49 Georgia America, 50 eSwatini, Uganda and Somalia 48 and Northwest Pakistan, 51 while different from the report from India which showed that the most prevalent mutation was eis C (−12)T (46.1%). 52 As for the SLID resistance, the RDBH assay showed 51.9% sensitivity and 100% specificity compared to the phenotypic DST.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, among 27 SLID resistant isolates, the most frequent mutation detected was rrs A1401G (40.7%), which was consistent with the reports from China, 4,6,49 Georgia America, 50 eSwatini, Uganda and Somalia 48 and Northwest Pakistan, 51 while different from the report from India which showed that the most prevalent mutation was eis C (−12)T (46.1%). 52 As for the SLID resistance, the RDBH assay showed 51.9% sensitivity and 100% specificity compared to the phenotypic DST.…”
Section: Discussionsupporting
confidence: 86%
“…Whole-genome sequencing has emerged as a new diagnostic tool that assists in clinical decision making in infectious diseases (Jabbar et al, 2019 ). The whole-genome sequencing of tuberculosis isolates provides genomic information that is responsible for causing resistance (Cohen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 61 ] According to a study in Pakistan in 2019, the majority of M. tuberculosis isolates were CAS/Delhi strain-type and MDR (76.5%), and mutations with resistance were observed in kat G, rpo B, pnc A, embB , gyr A, rrs , rps L, and rrs genes. [ 62 ] Drug-resistant TB isolates and their genes circulate among the population and they are transmitted between different communities worldwide. Therefore, performing more epidemiological studies and designing appropriate disease control plans are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, performing more epidemiological studies and designing appropriate disease control plans are of great importance. [ 2 62 ] In this study, embB codon 306 was investigated. Since other codons of this gene contribute to the development of EMB resistance as well, thus, it is advisable to research the rate of association of other codons with EMB resistance, in terms of systematic review and meta-analysis, to obtain comprehensive results.…”
Section: Discussionmentioning
confidence: 99%